An integrated industrial risk assessment methodology for accident safety, chronic health, and chemical exposure - Pons, Dirk (New Zealand Journal of Health and Safety Practice, 2024)
Context – Industrial safety primarily uses ISO31000 risk assessment based on consequence and likelihood to anticipate and prevent accidents. The method focuses on avoiding the occurrence of temporally immediate biophysical harm. Chronic health conditions are more difficult to include, as the harm is not necessarily immediate and the consequences can remain long after the hazardous event is removed. Furthermore the consequence scales vary for the different hazards. In the case of chemical hazards, the Globally Harmonised System (GHS7) measures these by severity (dose required for death), but this metric is incompatible with the graduated harm scales used in ISO31000. Consequently it is difficult to include chemical hazards in the methods used for other workplace hazards. There is a need for a single integrated method that can accommodate all aspects of industrial safety. Approach – The GHS7 chemical exposure scale is reworked and extended to non-death outcomes to make it compatible with the ISO31000 Risk management approach. Originality – A set of three harmonised consequence scales are developed for safety (immediate accident consequences), health (long term & chronic ill-health), and chemical exposure (death as well as less severe outcomes). This allows a single ISO31000 compliant methodology to be used.